Performance of blueberry seedlings obtained by micropropagation or cutting - de Souza, André Luiz Kulkamp; Schuch, Márcia Wulff; Antunes, Luís Eduardo Corrêa; Schmitz, Juliano Dutra; Pasa, Mateus da Silveira; Camargo, Samila Silva; Carra, Bruno (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the vegetative development and the onset of the productive period of blueberry (Vaccinium virgatum) seedlings obtained by semi-hardwood cuttings or micropropagation. In 2009, a blueberry orchard was established with one-year-old seedlings, at 1.3x4.0 m spacing. The cultivars Bluegem, Briteblue, and Woodard, from the rabbiteye group were utilized. The following parameters were evaluated: plant height, number and diameter of shoot, berry average diameter, number of harvested fruit per plant, average production per tree, estimated yield by hectare, fresh matter per fruit, content of soluble solids, titratable acidity and pH. Plants originated from the micropropagation technique showed high rate of initial vegetative growth, due to the rejuvenation caused by this sort of propagation. Propagation methods did not affect fruit quality. Despite the expected, micropropagated plants showed no delay in the initial fruit production and its fruit yield and quality were similar to those of cutting-propagated plants.